2011
DOI: 10.1055/s-0031-1280796
|View full text |Cite
|
Sign up to set email alerts
|

Medical, Psychological and Intellectual Development of 5-Year-Old Children Born after Intracytoplasmic Sperm Injection

Abstract: Once severe congenital anomalies were excluded, there were no differences in physical and neurodevelopmental outcome of 5-year-old ICSI children compared with controls.With regard to behaviour and emotional development, ICSI children seem to be similar or might be even more stable and socially competent than the control children. As our study is limited by the small sample size, further research is needed to confirm our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The age of the children in these studies ranged from 1.5 to 6.4 years. The majority of the studies did not show any association between conception following IVF or ICSI and childhood weight and height; however, a few studies found larger height in childhood among children exposed to IVF compared with spontaneously conceived controls. Miles et al.…”
Section: Resultsmentioning
confidence: 60%
See 4 more Smart Citations
“…The age of the children in these studies ranged from 1.5 to 6.4 years. The majority of the studies did not show any association between conception following IVF or ICSI and childhood weight and height; however, a few studies found larger height in childhood among children exposed to IVF compared with spontaneously conceived controls. Miles et al.…”
Section: Resultsmentioning
confidence: 60%
“…A total of seven of the included 20 studies did not report child weight and/or height in means and standard deviations in the published paper or upon request to the author . The age of the children in these studies ranged from 1.5 to 6.4 years.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations